AUGMENTED REALITY (AR) BASED KIDNEY ORGAN HANDOUT IS PRACTICAL IN HELPING CLASSICAL LEARNING OUTCOME OF HIGH SCHOOL STUDENTS - Wulandari, Siti; Priantari, Ika; Prafitasari, Aulya Nanda (ScienceEdu, 2025)
Biology learning is often perceived as difficult by students due to the abundance of abstract material, including the topic of kidney organs in the excretory system. This topic requires specific visualization to help students understand the concepts more easily and thoroughly. Therefore, this study aims to develop an Augmented Reality (AR)-based kidney organ handout as a practical learning medium to help high school students achieve mastery learning. This research employed a practicality instrument in the form of student response questionnaires and learning outcomes through a post-test. The students' practicality assessment showed a "very practical" category, with a percentage of 91.45%. Student learning outcomes after using the handout showed a minimum mastery criterion of 82.75%, exceeding the minimum threshold. Based on these results, it can be concluded that the AR-based kidney organ handout is a highly practical learning medium that can support high school students in achieving learning mastery.